Hang-back retropozice jako varianta oslabení okohybných svalů - Odehnal, M; Malec, J; Hlozánek, M (Ceska a slovenska oftalmologie, 2003)
In a clinical study the authors evaluate efficiency of the operation on oculomotoric muscles by the hang-back retroposition method. A total of 70 children have been operated on, 52 of the patients suffering from esotropia and 18 from exotropia. The mean preoperation deviation in esotropia was 30 +/- 12 pdpt, the postoperation deviation was in the range of 6 +/- 7 pdpt. In the exotropia cases the preoperation deviation improved from original 76.9%, in the exotropia group being 77.8%. The overall success rate of the hang-back retroposition in all these patients was 77.1%. Ina group of children operated on by a traditional retroposition there was an overall success rate 78.7% (77.6% in esotropia and 82.4% in exotropia cases). Hang-back retroposition has been equally effective as the traditional retroposition of oculomotoric muscles. Its main advantages include visibility of the operation field, minimum risk of perforation of sclera and a fair time factor of the intervention. The authors discuss the development, indications, further advantages but also possible disadvantages or limitations of this acknowledged surgical procedure in strabology.
Keywords: kojenec; Infant; Oculomotor Muscles; předškolní dítě; Child, Preschool; lidé; Ophthalmologic Surgical Procedures; Strabismus; oftalmologické chirurgické výkony; okulomotorické svaly; strabismus; Humans